#Shemergency: Use of a Professional Development Group to Promote Female Resident Recruitment and Retention. (February 2020) - Khatri, Utsha G.; Love, Jennifer; Zeidan, Amy; Hsu, Cindy H.; Mills, Angela M.
Abstract : Problem: Gender inequity in academic medicine is a pervasive challenge. Recommendations have been implemented to reduce inequities for female faculty. However, there are no well-established guidelines for the recruitment and retention of female residents. Approach: To address challenges faced by female physicians and support the recruitment and retention of female residents, female emergency medicine residents and attending physicians at the Hospital of the University of Pennsylvania formed a professional development group (PDG), #Shemergency, in July 2017. From July 2017 to July 2018, this PDG developed events and initiatives for female residents that addressed methods to improve awareness of and develop skills relevant to well-described gender disparities in mentorship, speakership and conference representation, compensation, evaluations, wellness and service, and award recognition. Outcomes: Over its first year (July 2017–July 2018), the PDG created a professional community and enhanced mentorship through a number of events and initiatives. The PDG secured funding for 5 residents to attend a national conference and nominated 5 residents and 2 attending physicians for professional organization awards (4 nominees won). Next Steps: After the first year, the PDG expanded the number of joint activities with both male and female colleagues and organized a citywide event for female residents and faculty representing 5 different residency programs. Future work will focus on sustainability (e.g., holding fundraising events), generalizability (e.g., expanding the gender-disparity areas addressed as well as spreading the model to other programs), developing additional events and initiatives (e.g., expanding the number of joint activities with male colleagues), and outcome assessments (e.g., distributing pre- and postevent surveys).